2007
DOI: 10.1016/j.jbusres.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical affect, student interest, and learning performance

Abstract: Using a sample of over 1000 students, this study reveals that student perceived learning depends directly on their interest and behavior (pedagogical affect and learning performance), and indirectly on student/instructor interaction, responsiveness, organization, liking/concern and learning performance. Student interest is indirectly affected by liking/concern through its influence on learning performance. Recommendations for schools, department heads and university administrators are addressed. Directions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
65
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 23 publications
8
65
1
7
Order By: Relevance
“…Abrantes and colleagues used path analysis to determine that learning performance predicts perceived learning (b 5 0.23) and perceived learning can predict better course evaluations. 13 However, this study found that pedagogical affect, such as instructional methods (b 5 0.31) and student interest (b 5 0.50), were stronger predictors of perceived learning. While the correlation coefficient for comfort and instructor evaluation was high (r 5 0.60), the small sample size (n 5 6) results in high variability, which may be a limiting factor in finding a significant correlation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Abrantes and colleagues used path analysis to determine that learning performance predicts perceived learning (b 5 0.23) and perceived learning can predict better course evaluations. 13 However, this study found that pedagogical affect, such as instructional methods (b 5 0.31) and student interest (b 5 0.50), were stronger predictors of perceived learning. While the correlation coefficient for comfort and instructor evaluation was high (r 5 0.60), the small sample size (n 5 6) results in high variability, which may be a limiting factor in finding a significant correlation.…”
Section: Discussionmentioning
confidence: 57%
“…Student interest reflects attention level in class, interest in learning the material, perception of the intellectual challenge of a course, and acquired competence. 13 Student interest is important in part because it facilitates effective teaching and creates a more favorable learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the perception of learning. Abrantes and colleagues 19 found that factors of course organization, student-instructor interaction, instructor responsiveness, and instructor likeability all positively impact perceived learning. According to the course evaluations, there was no difference in attitudes toward course organization or the instructor's approachability between the current and previous year's courses.…”
Section: Discussionmentioning
confidence: 99%
“…Students felt they missed out less on instructor interaction during the smaller-group format than during the TBL year. Given that student-instructor interaction plays a smaller relative role in the perception of learning than does instructor responsiveness, 19 it is surprising that students felt they missed out on learning. This lower extent of perceived learning may better relate to the intellectual development of students and the role peers play in the learning process.…”
Section: Discussionmentioning
confidence: 99%